Assessment of prognostic value of tissue inhibitors of metalloproteinase 3 (TIMP3) protein in ovarian cancer. Issue 1 (1st January 2021) - Hakamy, Sahar; Assidi, Mourad; Jafri, Mohammad A.; Nedjadi, Taoufik; Alkhatabi, Heba; Al-Qahtani, Abrar; Al-Maghrabi, Jaudah; Sait, Khalid; Al-Qahtani, Mohammed; Buhmeida, Abdelbaset; Chaudhary, Adeel
ABSTRACT: Background : TIMP3 is a multifunctional proteolytic enzyme belonging to TIMPs family and acts as a potent inhibitor of matrix metalloproteinases (MMPs). TIMP3 possesses a tumor suppresive function by directly promoting tumor cell apoptosis, preventing angiogenesis and extracellular matrix remodelling. The lower expression of TIMP3 was associated with poor prognosis and overall survival in various cancer types. The aim of this study was to evaluate the association of TIMP3 protein expression with ovarian cancer (OC) clinicopathological features and survival outcomes.Patients and Methods : One hundred forty four of OC FFPE samples were collected from King Abdulaziz University Hospital, Saudi Arabia and constructed in tissue microarray (TMA) slides. Automated Ventana immunostainer platform was used to evaluate TIMP3 protein expression patterns.Results : The study showed that TIMP3 exhibits cytoplasmic localisation. This TIMP3 protein expression was not associated with age, tumor size and the involvement of lymph nodes ( p > 0.05). However, it was significantly correlated with tumor stage ( p < 0.05) and borderline significant with endpoint status ( p = 0.07). Interestingly, the Kaplan-Meier analysis of disease specific survival (DSS) outcomes showed a significant association ( p = 0.02, log rank) between OC patients with higher TIMP3 expression compared to those with lower expression. In fact, OC patients with high TIMP3 expression had longer survivals. Multivariate Cox's regression analysis suggests that low TIMP3 protein expression pattern is an independent poor survival marker ( p = 0.025).Conclusion : Cytoplasmic TIMP3 protein expression could be used as a good prognosticator to stratify poorly prognostic OC patients in order to personlaize their disease management.